Collaborative Learning and Summarizing Strategy in Teaching Writing during COVID-19 Pandemic - Sri Rahmadhani Siregar (J-SHMIC : Journal of English for Academic, 2023)
The teaching and learning procedure was stated to be online in response to the COVID-19 pandemic.It is necessary to change from face-to-face instruction to online learning. In accordance with this, teachers must modify their online teaching and learning practices. This study concentrated on the methods teachers used to implement teaching writing throughout the epidemic COVID-19. The study's goals are to outline the teacher's approach to teaching writing and how to use it in widespread online learning. The study adopted a qualitative descriptive method. The participants of this research are two English teachers. The data were collected by using observation, interviews, and documents. Respondents were observed during the teaching learning process and interviewed to support observation data. The data collected were analyzed by using Creswell’s procedures which were organizing, preparing, looking, reading, coding, and interpreting data. The findings of this research concluded that from various strategies of teaching writing, the English teacher only implemented a collaborative learning strategy and summarizing strategy. Following the pandemic situation, the two strategies were done online through the zoom platform. By doing this research, it suggested that teachers adopt and practice more strategies in teaching, not only teaching writing but also teaching all skills in English.